The spectrum of eigenvalues for certain subgraphs of the k -point fixing graph - Ku, Cheng Yeaw; Lau, Terry; Wong, Kok Bin (Elsevier, 2018)
Let Sn be the symmetric group on n-points. The k-point fixing graph F(n,k) is defined to be the graph with vertex set Sn and two vertices g, h of F(n,k) are joined if and only if gh−1 fixes exactly k points. In this paper, we give a recurrence formula for the eigenvalues of a class of regular subgraphs of F(n,k). By using this recurrence formula, we will determine the smallest eigenvalues for this class of regular subgraphs of F(n,1) for sufficiently large n.